Revisiting the EPS : A Path-Breaking Approach Toward Performance Measurement in the Capital Markets : A Case Study of Reliance Industries Ltd. - Gupta, Ambrish (Indian Journal of Research in Capital Markets, 2023)
The most widely recognized and quoted measure of company success in the capital market is earnings per share (EPS). It does, however, have a major flaw. Due to the fact that it was only calculated using the equity component of the entire equity, the results conflicted with return on equity (ROE), which is calculated with reference to total equity. Consequently, even while the numerator, or profit after tax (PAT), remained the same, the denominator of the two ratios varied. As a result, EPS indicated a larger return than ROE. This made it difficult for analysts and investors to decide which metric to employ when making investments or disinvestments. Making a choice based only on EPS could have disastrous effects on the money invested. Thus, there is a requirement for an extensive EPS measurement so that it produces precise and comprehensive findings. Can we then go back and modify the EPS measurement to make it more reasonable and in accordance with ROE? We really can, in fact. We might do this by classifying all equity as equity capital since ownership by shareholders is derived from both equity capital and other equity, which is represented by reserves and surplus. Stated differently, the whole of the preceding equity capital and other equity would represent the resulting equity capital if accumulated reserves and surplus were allocated as bonus shares. Earnings per share of total equity (EPS-TE), often known as the path-breaking ratio, can now be calculated. Once this revolutionary concept was applied to the EPS of Reliance Industries Ltd., EPS-TE was computed, and the outcomes demonstrated that EPS and ROE were now precisely in sync.